STUDY ON DUCTILE FRACTURE CRITERION PARAMETERS OF HIGH STRENGTH DUPLEX STEEL PLATE - MA ChunHui; ZHANG DianPing; GONG ZeFei; LIU XingFeng; SONG Hui; LI Di (Jixie qiangdu)
In order to predict the ductile fracture failure of different high-strength steel plates, the damage parameters of the ductile fracture criterion were calibrated by designing the tensile, shear and fracture failure tests of four high-strength steel plates. The relation between damage parameters and material properties is established by combining test and numerical simulation, so as to reduce the difficulty of calibrating the damage parameters of ductile fracture criterion. In order to verify the universality and accuracy of the criterion in predicting the fracture failure of high-strength steel under different stress triaxiality, through shear, tension bending, bulging test and numerical simulation. The results show that the ductile fracture criterion can better predict the fracture failure of different advanced high strength steels.